Perbandingan Loyalitas Pelanggan Pengguna Top 5 Aplikasi Dompet Digital (Shopee Pay, OVO, DANA, Go-Pay, dan Link Aja) (Studi Kasus Pada Pengguna di Jabodetabek) - Permatahati, Indah Putri; Djamaris, Aurino Rilman Adam (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
Many applications have emerged that providepayment transaction services digital, which are now growing rapidly with the increasing number of users, such as the Shoppe Pay, OVO, Dana, Go-Pay, andapplications Link Aja. The purpose of this research is to compare Customer Loyalty of users of theWallet Application Digital. This study was conducted on users of the Shoppe Pay, OVO, Dana, Go-Pay, andapplications Link Aja in the Greater Jakarta area. This type of research uses a comparative problem, namely comparing the existence of a variable in five samples. This study usesinstrument (questionnaire) a Likert scale as a study of 114 respondents. The instrument testing technique uses Validity and Reliability Test, the result is that each item of the instrument used is valid and reliable. The data analysis technique used is ANOVA analysis One Way. The result of the comparison data processing, there are significant differences.